PENGARUH PENERAPAN ATURAN ETIKA, PENGALAMAN AUDITOR, DAN SKEPTISME PROFESIONAL TERHADAP PENDETEKSIAN KECURANGAN LAPORAN KEUANGAN - M Rizki Rinaldi; Rita Anugerah; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research aims to examine the Influence of Application Profesion Ethic, Audit Experience, and Professional Skepticism in Detection of the Fraud. Object of this research are the accountants public offices in Pekanbaru, Padang, Palembang and Batam. This research use primary data. There are fifty three questionnairs which are sent but, only forty nine questionnairs returned. Data of this research is analyzed by multiple regression method. The results of this research showed that the application of profesion ethic has no effect in detection of the fraud with 0,058 significance, audit experience has an effect in detection of the fraud with 0,008 significance, and professional skepticism has an effect in detection of the fraud with 0,000 significance. The results of this research also showed that coefficient determinant is 75,8%. Each independent variables, give the strong influence to dependent variable, it means independents variables could explain dependent variable well. While the remaining influenced by other variables not included in the regression models were not included in this study as professional commitment, audit’s pressure and others.Keywords: Profesion Ethic, Auditor, Professional, Fraud, and Financial Statement